What goes around comes around: The integrated role of emotions on consumer ethical decision‐making - Escadas, Marco (2020)
The current study aims to further our understanding of the integrated role of emotions on consumer decision making involving ethical issues, by considering the influence of both positive and negative emotions on ethical decision making process. It considers not only the emotions experienced prior to ethical decision making (pre-decision emotions) but also those resulting from the course of action chosen (post-decision emotions). Scenarios are used, and the results of the structural modelling analyses support the proposed relationships between current emotions, consumers’ ethical decision making, post-decision emotions and future ethical behavioural intentions. The data suggest the possible existence of a “virtuous ethical cycle”, whereby positive emotions lead to more ethical consumer decisions and behaviours; and these in turn lead to more positive (post-decision) emotions, which have a positive and significant effect on future ethical behavioural intentions. In addition, happiness emerges as exerting a pivotal role in predicting consumer ethical decisions.